Analysis of Criminalization of Children Who Commit the Crime of Narcotics Trafficking - Dwi Mika Elencia Sirait; Janpatar Simamora; Jinner Sidauruk (Journal of Legal and Cultural Analytics, 2025)
This consider analyzes the criminalization of children who commit the wrongdoing of opiates trafficking, as committed by children could be a genuine issue that requires extraordinary taking care of since children are the nation's era. The reason of this think about is to discover out the application of the criminal law for opiates trafficking wrongdoings committed by children and to know lawful cures in diminishing opiates trafficking wrongdoings committed by children. The inquire about strategy employments standardizing juridical with a administrative approach and a case approach. This think about concludes that the treatment of children is distinctive from grown-ups and there are legitimate measures that can be taken to decrease opiates wrongdoings committed by children.